Analisis Kemampuan Matematika Siswa SMP BSS Ditinjau dari Tingkat Beban Kognitif dan Motivasi Intrinsik - Ervan Dwi Yuliaristiawan; Muhammad Rifqy Ramadana; Yerry Soepriyanto; Purnomo Purnomo (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Mathematics education in middle school was important for developing students' logical and analytical thinking abilities. This article explored the factors influencing students' mathematical abilities, particularly cognitive load and intrinsic motivation. Cognitive load referred to how much information students could process, which could hinder understanding if too high. Intrinsic motivation increased students' enthusiasm for learning and encouraged deeper understanding. This research analyzed the relationship between BSS middle school students' mathematical abilities and their levels of cognitive load and intrinsic motivation through data collection. Data analysis was conducted using multiple regression tests to determine the relationship between students' cognitive load and intrinsic motivation levels and their mathematical abilities both in mathematics subjects and simultaneously. The multiple regression statistical test showed that intrinsic motivation did not significantly affect students' mathematical abilities (sig.0.102>0.05), while students' cognitive load significantly affected their mathematical abilities but was weak (sig.0.021<0.05). Simultaneously, the influence of cognitive load and intrinsic motivation significantly affected students' mathematical abilities (0.01<0.05). This research provided suggestions for further research on the impact of cognitive load on students' mathematical abilities.